2013
DOI: 10.1093/annonc/mdt249
|View full text |Cite
|
Sign up to set email alerts
|

A phase I/II study of sepantronium bromide (YM155, survivin suppressor) with paclitaxel and carboplatin in patients with advanced non-small-cell lung cancer

Abstract: NCT01100931.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
119
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 134 publications
(123 citation statements)
references
References 19 publications
3
119
0
1
Order By: Relevance
“…Our data demonstrate that YM155 exerts cell growth inhibition effects synergistically with gemcitabine. This is consistent with reports that YM155 enhances the anti-tumor effects of other chemotherapeutic agents including: cisplatin, rituximab and paclitaxel (14, 19, 34, 48, 49). Our study raises the potential prospect of using YM155 and gemcitabine in combination for pancreatic cancer therapy.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our data demonstrate that YM155 exerts cell growth inhibition effects synergistically with gemcitabine. This is consistent with reports that YM155 enhances the anti-tumor effects of other chemotherapeutic agents including: cisplatin, rituximab and paclitaxel (14, 19, 34, 48, 49). Our study raises the potential prospect of using YM155 and gemcitabine in combination for pancreatic cancer therapy.…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, we demonstrate YM155 can induce apoptosis in pancreatic cancer cells at clinically relevant doses. The reported plasma concentration is approximately 15 nM (12, 13, 34). Our study suggests that YM155 may have potential use as a systemic therapy for pancreatic cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Several clinical studies of YM155 revealed that it was very well tolerated, but likely would be best utilized in combination chemotherapy due to its limited single-agent efficacy (44)(45)(46)(47)(48). Multiple combination studies with YM155 were conducted with paclitaxel or docetaxel regimens based on the rationale that YM155 may be able to overcome taxane-mediated upregulation of survivin expression, which promotes drug resistance (44,(48)(49)(50).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple combination studies with YM155 were conducted with paclitaxel or docetaxel regimens based on the rationale that YM155 may be able to overcome taxane-mediated upregulation of survivin expression, which promotes drug resistance (44,(48)(49)(50). However, the lack of efficacy that was observed in these clinical studies may have been due to incomplete suppression of survivin levels in the tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Disruption of Survivin causes impaired chromosome movements, spindle checkpoint override and polyploidy [ 190 ], suppressing cell proliferation [ 191 ]. YM155, a drug that interferes with induction of the Survivin promoter, has entered clinical trials, with inconclusive results thus far in non-small-cell lung cancer [ 192 ]. Another drug, S12, that allosterically blocks Survivin interactions with CPC binding partners, shows promise as an inhibitor of tumor growth in vivo [ 193 ].…”
Section: Spindle Protein Inhibitorsmentioning
confidence: 99%